Sustainable Development Strategy for Chinese Infrastructure Firms in Central Asia - Tian Qi (World Scientific Reports, 2026)
Under the framework of the Belt and Road Initiative (BRI), efficient cross-border infrastructure investment and operation have emerged as a core pillar underpinning economic and trade cooperation between China and Central Asian nations. The traditional extensive development model adopted by Chinese infrastructure firms operating in Central Asia is facing growing constraints from geopolitical risks, environmental regulations, social governance requirements, and regional sustainable development goals. This study explores a systematic path for the sustainable development of Chinese infrastructure firms in the Central Asian market. Based on in-depth case studies and field interviews, the research finds that green infrastructure development, ESG governance, geopolitical risk management, and localized operation constitute the core practical focuses in this field. On this basis, the study identifies the core opportunities for Chinese infrastructure firms in Central Asia, sorts out the major challenges they encounter, and ultimately constructs a five-dimensional sustainable development strategic system (its core logic is rooted in the three dimensions of economic, environmental and social sustainability), along with targeted implementation paths for enterprises.